Использование полимеразной цепной реакции для идентификации ДНК гельминтов из родов fasciola, echinococcus и trichinella - Мангасарян, Р. Г.; Асатрян, А. М.; Семенова, С. К. (Մանկավարժ հրատ․)
В работе применен метод полимеразной реакции (ПЦР) для идентификации родов Fasciola, Echinococcus и Trichinella. Доказано, что метод можно использовать в филогенезе и систематике гельминтов. Աշխատանքում կիրառվել է պոլիմերազային շղթայական ռեակցիաների մեթոդը՝ Fasciola, Echinococcus և Trichinella սեռի հելմինթների տարբերակման համար: Ապացուցված է, որ նշված մեթոդը կարելի է օգտագործել հելմինթների ֆիլոգենեզում և կարգաբանությունում: We have used the polymeraze chain reaction (PCR) and random amplified polymorphic DNA (RAPD) method to identify DNA polymorphisms to characterized three classes of helminths: Cestoda and Nematoda. In this study, RAPD markers have been used to description of genetic variability between the families, genus, species and isolates of helminths. We optimised the conditions of RAPD analyses and revealed the genetic variability of helminyhs belonding to the same different taxonomic groups. This results show that the RAPD-PCR method can be considered as a suitable technique for helminths phylogenetic identifications. It was discussed the problems of age – and hostspecificity taxons.
Keywords: Биология